KRITIK TERHADAP PENAFSIRAN COACH MENTOR POLIGAMI DAN REPRODUKSI KETIMPANGAN GENDER DI MEDIA SOSIAL - Shofiatun Nikmah; Risma Hikmawati; Mokhammad Samsul Ikhsan; Achmad Fuaddin (STAI AL-ANWAR SARANG, 2024)
This research examines the critique of polygamy mentors to interpretations of the verse on polygamy in Islam that are rampant on social media, especially through polygamy mentoring programmes. Polygamy mentors such as Hafidhin and Riski Ramdhani interpret QS. Al-Nisa and 34 as legitimate to practice polygamy, without considering aspects of gender justice. The narrative they build leads to the glorification of polygamy as a sharia that is worthy of worship, with minimal attention to the social and psychological impacts on women. This study uses a critical approach and gender hermeneutics to analyse how polygamy mentor interpretations are used as ideological tools in reproducing gender inequality. Through analysis of their interviews and podcasts, it was found that their paradigm of thought positions women as objects that must be designed to accept polygamy, with a doctrine that limits women's rights and freedoms. The results show that polygamy mentor interpretations of polygamy have shifted from their original purpose in the Quran, as a solution to certain social problems, to an instrument of domination that ignores the principles of equality and justice. Criticism of this understanding asserts that the verse on polygamy does not mean an absolute recommendation, but as a form of regulation of existing practices in society at that time. Therefore, a more contextual and equitable reinterpretation is needed so that the interpretation of polygamy is not used as a tool to perpetuate gender inequality.